Large-scale analyses of angiosperm Flowering Locus T genes reveal duplication and functional divergence in monocots - Liu, Hongling; Liu, Xing; Chang, Xiaojun; Chen, Fei; Lin, Zhenguo; Zhang, Liangsheng (Frontiers in Plant Science, 2023)
FLOWERING LOCUS T (FT) are well-known key genes for initiating flowering in plants. Delineating the evolutionary history and functional diversity of FT genes is important for understanding the diversification of flowering time and how plants adapt to the changing surroundings. We performed a comprehensive phylogenetic analysis of FT genes in 47 sequenced flowering plants and the 1,000 Plant Transcriptomes (1KP) database with a focus on monocots, especially cereals. We revealed the evolutionary history of FT genes. The FT genes in monocots can be divided into three clades (I, II, and III), whereas only one monophyletic group was detected in early angiosperms, magnoliids, and eudicots. Multiple rounds of whole-genome duplications (WGD) events followed by gene retention contributed to the expansion and variation of FT genes in monocots. Amino acid sites in the clade II and III genes were preferentially under high positive selection, and some sites located in vital domain regions are known to change functions when mutated. Clade II and clade III genes exhibited high variability in important regions and functional divergence compared with clade I genes; thus, clade I is more conserved than clade II and III. Genes in clade I displayed higher expression levels in studied organs and tissues than the clade II and III genes. The co-expression modules showed that some of the FT genes might have experienced neofunctionalization and subfunctionalization, such as the acquisition of environmental resistance. Overall, FT genes in monocots might form three clades by the ancient gene duplication, and each clade was subsequently subjected to different selection pressures and amino acid substitutions, which eventually led to different expression patterns and functional diversification. Our study provides a global picture of FT genes’ evolution in monocots, paving a road for investigating FT genes’ function in future.